Kinerja ESG, Independensi Komite Audit, dan Biaya Modal: Bukti Moderasi dari Perusahaan Bursa Efek Indonesia - Hotma Glorya Ika Sari; Lady Karlinah; Liem Yan Sugondo; Amelia Ananta (Politeknik Ganesha Medan, 2026)
This study investigates the effect of Environmental, Social, and Governance (ESG) performance on firms' cost of capital and examines the moderating role of audit committee independence in an emerging market context. The sample consists of 95 companies listed on the Indonesia Stock Exchange (IDX) during the period 2016–2023, resulting in 760 firm-year observations in a balanced panel dataset. Using panel data regression with a moderating approach, the findings indicate that ESG performance has a negative and significant effect on the cost of capital, with a one-point increase in ESG score reducing the weighted average cost of capital (WACC) by approximately 13.6 basis points. Audit committee independence also exhibits a negative effect on the cost of capital. However, the interaction analysis reveals that audit committee independence significantly weakens the negative relationship between ESG performance and the cost of capital, suggesting that the financial benefits of ESG practices are less pronounced when governance oversight is already strong. Theoretically, this study extends signaling theory by demonstrating that the credibility of ESG signals depends on existing governance structures; empirically, it provides evidence from an emerging market where governance and sustainability disclosures are evolving. The findings offer practical insights for managers and investors in aligning ESG strategies with governance mechanisms to enhance financial efficiency.